Competing Through Categorization: Product- and Audience-Centric Strategies in an Evolving Categorical Structure. Issue 7 (July 2019) - Kodeih, Farah; Bouchikhi, Hamid; Gauthier, Valérie
We investigate how and why competing organizations position their similar products in categories of varying status. We studied the paired longitudinal case of the highly publicized contest between ESSEC and HEC, two French business schools, as they sought to position their core Grande Ecole program in the evolving international business education categorical structure. We conceptualize categorization as a competitive, relational process involving multiple actors and producing various meanings and perceptions. Our study (a) highlights the role of anticipated category status spillovers versus anticipated relative status within a category in producers' entry decisions; (b) contrasts product- and audience-centric categorization strategies; and (c) shows the role of intermediaries in adjudicating categorization contests.